The influence of culture on crime and the impact of national development banks on regional growth - Zanchi, Vinicius Vizzotto (2019)
The first part of this thesis evaluates whether people in highly individualistic cultures have a lower propensity to commit violent crimes using cross-section data from 74 countries. Several previous papers report a significant negative correlation between these two variables, but it is not well established whether the effect of culture on crime is direct or indirect. My results show that individualistic nations generate a more effective juridical system which is mainly responsible for the variation in homicide rates across countries. It turns out that individualism affects crime only indirectly because the quality of legal institutions has a moderating effect. Economic or political institutions have a similar relation to the degree of individualism, however, the moderating effect on crime is only present for legal institutions. The second part analyzes whether the earmarked loans provided by the Brazilian Development Bank (BNDES) have an impact on the GDP growth of municipalities. I use dynamic panel data techniques with spatial dependence and the System-GMM estimator to evaluate the 5,504 municipalities between 2007 and 2016. Several previous papers report that credit offered by this bank has no impact on investments and productivity of large companies. However, since Brazil has a continental dimension and banking presence is still precarious in poor cities and distant from large agglomerations, the presence of BNDES’ loans may be relevant. My results show that the indirect loans of the BNDES, generally for small and medium firms and mandatorily disbursed through commercial banks, as well as non-earmarked credit from commercial banks, positively contribute to regional economic growth. On the other hand, the direct BNDES loans did not show pertinent influence.